RADIANCE – Radiochemotherapy with or without Durvalumab in the treatment of anal squamous cell carcinoma: A randomized multicenter phase II trial. (July 2020) - Martin, Daniel; Balermpas, Panagiotis; Gollrad, Johannes; Weiß, Christian; Valentini, Chiara; Stuschke, Martin; Schäfer, Henning; Henkenberens, Christoph; Debus, Jürgen; Krug, David; Kuhnt, Thomas; Brunner, Thomas; et al.
Highlights: The 3-year disease-free survival of locally-advanced anal carcinoma is about 60%. Anal carcinoma is considered an immunogenic tumor due to its association with HPV. The PD-L1 inhibitor durvalumab may synergize with radiochemotherapy. The RADIANCE trial will test durvalumab with radiochemotherapy in anal carcinoma. Abstract: Purpose: Anal squamous cell carcinomas (ASCC) are increasing in frequency across the developed world. The 3-year disease-free survival (DFS) in patients with locally-advanced disease is approximately 60% after primary radiochemotherapy (RCT). There is a strong rationale for combining immunotherapy with RCT in patients with ASCC due to its association with human papilloma virus (HPV) infection. Methods/design: RADIANCE is an investigator initiated, prospective, multicenter, randomized phase II trial testing the addition of Durvalumab, a PD-L1 immune checkpoint inhibitor, to standard RCT in 178 patients with locally advanced ASCC (T2 ≥ 4 cm Nany, cT3-4 and/or cN+). In the control arm, patients will be treated with standard mitomycin C (MMC)/5-fluorouracil (5-FU)-based RCT. Intensity-modulated radiotherapy (IMRT) will be applied as follows: PTV_A (primary tumor) T1-T2 < 4 cm N+: 28 × 1.9 Gy = 53.2 Gy; or T2 ≥ 4 cm, T3-4 Nany: 31 × 1.9 Gy = 58.9 Gy; PTV_N (involved node): 28 × 1.8 Gy = 50.4 Gy ; and PTV_Elec (elective node): 28 × 1.43 Gy = 40.0 Gy over a period of 5, 5–6 weeks. Concomitant chemotherapy will be administered using MMC with 5-FU during weeks 1 and 5 of radiotherapy (MMC 12 mg/m 2, day 1 [maximum single dose 20 mg]; 5-FU 1000 mg/m 2 days 1–4 and 29–32). In the experimental arm, Durvalmab (1500 mg absolute dose, intravenously) will be combined with the same RCT as in the control arm. Immunotherapy with Durvalumab will start 14 days before initiation of standard RCT, administered every four weeks (q4w) thereafter for a total of twelve doses. The primary endpoint is disease-free survival (DFS) after 3 years. Discussion: As ASCC is considered an immunogenically "hot" tumor due to its association with HPV infection, the combination of RCT with Durvalumab may improve tumor control and long-term clinical outcome in this patient collective compared to RCT alone.